2020
DOI: 10.1007/s10120-020-01137-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative chemotherapy as initial treatment for advanced gastric cancer with peritoneal metastasis limited to positive peritoneal lavage cytology (CY1) or localized peritoneal metastasis (P1a): a multi-institutional retrospective study

Abstract: Background Gastric cancer (GC) patients with peritoneal metastasis are defined as stage IV in the Japanese classification of GC. For patients with peritoneal metastasis limited to positive peritoneal lavage cytology (CY1) and/or localized peritoneal metastasis (P1a), gastrectomy followed by S1 monotherapy is one of the most widely accepted therapeutic strategy in Japan. This study investigated the efficacy of preoperative chemotherapy as initial treatment in GC patients with CY1 and/or P1a. Methods We retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
2
15
1
Order By: Relevance
“…However, this may not be true in patients with type 4 or large type 3 GC. Furthermore, it has been reported that conversion to negative peritoneal cytology did not result in improved survival in GC [14]. This result also supports the negative association between histological response and survival in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…However, this may not be true in patients with type 4 or large type 3 GC. Furthermore, it has been reported that conversion to negative peritoneal cytology did not result in improved survival in GC [14]. This result also supports the negative association between histological response and survival in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Li et al [ 102 ] studied 51 gastric cancer patients with preoperative laparoscopic exploration, and reported that 13.7% (7/51) of patients with stage cT3 cancer and below developed CY1 gastric cancer. Other gastric lavage studies have shown similar results [ 103 , 104 , 105 , 106 , 107 ].…”
Section: Mmt Of Pmcs Promotes Tumor Progression In the Peritoneal Cavitysupporting
confidence: 70%
“…Currently, the prognosis of GC-CY 1 patients is poor, and there is no universal consensus on the most suitable treatment for these patients ( 5 , 8 ). Systemic chemotherapy has been widely accepted as the standard treatment for patients with stage IV and has been proved to improve the prognosis ( 9 ). However, due to the existence of peritoneal-plasma barrier, chemotherapeutic drugs cannot directly act on the abdominal cavity ( 10 ).…”
Section: Introductionmentioning
confidence: 99%